Professores E Gestão Pública No Processo De Elaboração De Planos De Carreira Do Magistério Público: O Caso Da Prefeitura Municipal De Campinas (2001-2004)" - Guimaraes, Ana Paula Kacenelenbogen [UNIFESP] (2018)
The Research Is Part Of The Field Of Study On The Professionalization And Appreciation Of Teachers In Public Teaching Profession, Having As Object Of Study The Process Of Restructuring The Career And Working Conditions Of The Public Teaching Profession Of The Municipality Of Campinas, During The Municipal Management Of The Workers' Party (2001-2004), And The Teacher Appreciation Resulting From It. The Purpose Of This Study Is To Analyze , On One Hand, The Process Of Elaboration Of The Restructuring Of The Career Path Of The Municipality Of Campinas, That Was At The End Of The Process Enshrined In Law 12.012/2004 Which Included Changes In Career Reorganization And Conditions Of Public Teaching In Campinas, And, On The Other Hand, The Teacher's Appreciation Which Resulted From This Law. This Process, Which Counted On The Participation Of Education Professionals, Extended Throughout The Government Of The Partido Dos Trabalhadores (Workers' Party) (2001-2004), Under The Mandate Of The Mayors Antônio Da Costa Sant